New trends in model and data engineering : MEDI 2018 International Workshops, DETECT, MEDI4SG, IWCFS, REMEDY, Marrakesh, Morocco, October 24-26, 2018, proceedings /: MEDI 2018 International Workshops, DETECT, MEDI4SG, IWCFS, REMEDY, Marrakesh, Morocco, October 24-26, 2018, proceedings. (2018) - Unknown
No abstract available